2013
DOI: 10.1111/1574-6941.12197
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial community in alpine grasslands along an altitudinal gradient on the Tibetan Plateau

Abstract: The Tibetan Plateau, 'the third pole', is a region that is very sensitive to climate change. A better understanding of response of soil microorganisms to climate warming is important to predict soil organic matter preservation in future scenario. We selected a typically altitudinal gradient (4400 m-5200 m a.s.l) along south-facing slope of Nyainqentanglha Mountains on central Tibetan Plateau. Bacterial communities were investigated using terminal restriction fragment length polymorphism analysis (T-RFLP) combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
78
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(87 citation statements)
references
References 62 publications
7
78
2
Order By: Relevance
“…These disparities most likely stem from the prevailing cold climate conditions in our study and that of Yergeau et al [9]. Soil microorganisms in cold environments have optimal growing temperatures far above field conditions [19], [42], which potentially enable them to increase their biomasses rapidly under elevated temperatures [43]. Therefore, temperature had a direct effect on microbial biomass.…”
Section: Discussionmentioning
confidence: 57%
“…These disparities most likely stem from the prevailing cold climate conditions in our study and that of Yergeau et al [9]. Soil microorganisms in cold environments have optimal growing temperatures far above field conditions [19], [42], which potentially enable them to increase their biomasses rapidly under elevated temperatures [43]. Therefore, temperature had a direct effect on microbial biomass.…”
Section: Discussionmentioning
confidence: 57%
“…It indicated that soil autotrophic microbial community structures were strongly regulated and driven by the variations of soil properties and climatic conditions resulting from elevation difference. This altitudinal distribution pattern was also exhibited in bacteria, archaea, ammonia oxidizers, and denitrifiers (Wang et al 2015;Yang et al 2014;Yuan et al 2014;Zheng et al 2014). VPA revealed a much lower individual explanation of each environmental factor to the community variation (≤10.3 %).…”
Section: Discussionmentioning
confidence: 81%
“…Climate warming has accelerated glacier melting (Ding et al 2006;Lutz et al 2014) and changed vegetation phenology (Jin et al 2013;Shen et al 2014) on the plateau. A few recent studies have revealed that soil bacteria, archaea, ammonia oxidizers, and denitrifiers were sensitive to environmental changes and exhibited clear elevational patterns (Wang et al 2015;Yang et al 2014;Yuan et al 2014;Zheng et al 2014). However, as a global biodiversity hotspot, Tibetan Plateau receives less attention in soil functional microbial communities and their response to environmental changes, especially in autotrophic microbial communities.…”
Section: Introductionmentioning
confidence: 99%
“…Despite their high biodiversity and critical ecological and economical roles, soil fungal communities are still poorly studied relative to soil bacterial communities (Anderson and Cairney, 2004;Pautasso, 2013). Soil pH is universally accepted as an overarching factor in determining the biogeographical distribution of soil bacterial communities in various studies (Fierer and Jackson, 2006;Nicol et al, 2008;Baker et al, 2009;Davis et al, 2009;Jenkins et al, 2009;Jones et al, 2009;Lauber et al, 2009;Chu et al, 2010;Shen et al, 2013), although exceptional findings have also indicated that soil parameters other than pH can have a significant influence (Hollister et al, 2010;Sul et al, 2013;Yuan et al, 2014). In contrast, there is no widely accepted conclusion related to the biogeographical distribution of soil fungal communities, and only a limited number of studies have indicated that the biogeographical distribution of soil fungal communities varies with ecosystems.…”
Section: Introductionmentioning
confidence: 99%